Association between Possible Sleep Bruxism and Anxiety Disorders, Circadian Cycle and Sleep Disorders in Children and Adolescents: A Cross Sectional Study - Larissa Soares-Silva; Claudia Tavares-Silva; Pedro Paulo Pires; Lucianne Cople Maia (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To evaluate the frequency and association between anxiety disorders (AD), sleep disorders (SD), and the circadian cycle (CC) with possible sleep bruxism (SB) in children/adolescents. Material and Methods: The clinical records of children/adolescents, between 7-11 years, who were treated at the pediatric dentistry clinic/UFRJ (January/2018 to March/2020), were evaluated. SCARED and CIRENS questionnaires and, SD were analyzed. The chi-square test, t-test, and Cohen’s D were applied. Results: Of 85 clinical records were evaluated, 41 (48.2%) were from girls and 44 (51.8%) from boys of 7 (3.5%), 8 (5.9%), 9 (25.9%), 10 (24.9%) and 11 (40%) years old. There were identified in 40 (47.1%) participants with AD, while SB was identified in 28 (32.9%). The most prevalent CC was "neither morning nor night" (75.3%), followed by "morning type" (20%). No association was found between CC and SB (p>0.05). Likewise, no association was found between AD and SB, SD and AD (p>0.05). However, an association was identified between SD and SB (p<0.05). In addition, the shorter the sleep duration, the greater the likelihood of bruxism (p<0.01). For effect size Cohen’s d was 0.955, considered large. Conclusion: It was not possible to identify an association between the CC and psychological factors, such as anxiety, with the presence of SB. However, sleep disorders and sleep duration demonstrated a relationship with sleep bruxism.